The brown bear (Ursus arctos) in Holocene Britain: a review of the evidence - O'Regan, Hannah J. (Wiley, 2018)
1. The brown bear, Ursus arctos, was Holocene Britain’s largest carnivoran and has appeared in recent rewilding discussions. 2. Despite widespread interest, we know very little about the species in Holocene Britain as few studies have been undertaken. This paper draws together information on the brown bear to examine the presence and extinction of bears through examination of the archaeological and palaeontological evidence. 3. Data were collected from published literature and museum catalogues. Information on the chronological date of the sites, number of specimens, and the body parts present were particularly sought. 4. A total of 86 sites were identified, 57 are well dated, 27 are of uncertain date but likely to be Holocene, and two have uncertain identifications. Very few specimens from non-archaeological sites (i.e. fens and caves) are well-dated, skewing the data towards anthropogenic sites such as settlements, castles, and graves. 5. Analysis of body part representation shows that the bear bones found in the Bronze Age, Iron Age and most of the early medieval period are from skins. All body parts are present during the Romano-British, medieval, and post-medieval period, indicating that live bears were present, and were probably imported for entertainment. 6. It seems the brown bear was rare throughout the Holocene, and based on current evidence two extinction scenarios can be put forward: extinction in the late Neolithic/early Bronze Age, or extinction in the early medieval period.